Development of an Ethno-Commognitive Based IEAC Learning Model to Improve TPACK of Prospective Mathematics Teachers - Zayyadi, Moh; Supardi, Lili; Linarsih, Yanti; Lanya, Harfin; Mosdalifah, Mosdalifah; Saputra, Andi (FKIP Universitas Lampung, 2023)
Development of an Ethno-Commognitive Based IEAC Learning Model to Improve TPACK of Prospective Mathematics Teachers. Objectives: Ethno-commognitive based IEAC learning model to improve the TPACK abilities of prospective mathematics teacher students. Methods: This type of research is development research. The development carried out in this research is a learning model consisting of a lesson plan, student worksheets, and ethno-commocognitive-based tests to improve the TPACK abilities of prospective teacher students in supporting independent learning. The development procedure used is the ADDIE model. Data analysis in this research is as follows: validation analysis, practicality analysis, and effectiveness analysis. Findings: Development of an ethno-commognitive based IEAC learning model to increase the TPACK of prospective mathematics teacher students to meet the criteria of valid, practical, and effective. Conclusion: Development of an ethno-commognitive based IEAC learning model to improve the TPACK abilities of prospective mathematics teacher students on number pattern material that meets the criteria of valid, practical and effective. Keywords: IEAC learning model, ethno-commognitive, TPACK.DOI: http://dx.doi.org/10.23960/jpp.v13.i3.202324